PENYULUHAN DAN PENCEGAHAN JUDI ONLINE SEBAGAI UPAYA MENINGKATKAN KESADARAN HUKUM MASYARAKAT DESA CIGUGUR GIRANG - Asep Dadang Hidayat; Yudi Khoeri Abdillah; Agung Wildan Azizi; Senki Nurachmadi; Ai Khomisah Alawiyah (Jurnal Istimā, 2025)
The increasing prevalence of online gambling within society has become a critical social issue, posing threats to moral values, psychological stability, and household economic welfare. This problem is exacerbated by the ease of digital access and the community’s limited understanding of legal consequences. This Community Service Programme (PKM) was conducted to enhance legal literacy and public awareness in Cigugur Girang Village regarding the risks and juridical implications of online gambling. The method employed involved legal counselling through material presentation, visual media, interactive discussions, and a question-and-answer session as an evaluative tool. The results indicated a significant improvement in public awareness, reflected in the participants’ active involvement, responsive engagement during discussions, and their ability to answer questions correctly. Furthermore, a collective commitment emerged among residents to reject online gambling and safeguard their social environment. Hence, this PKM activity contributes to preventive efforts against online gambling by strengthening legal awareness and community responsibility practically and sustainably.